Distributed Cooperative Multicell Precoding Based on Local Channel State Information - Jing An; Guofeng He; Youwu Xu; Bin Wang; Sen Xu (Universitas Ahmad Dahlan, 2015)
Cooperative multicell precoding is an attractive way of improving the performance in multicell downlink scenarios especially for terminals at cell edges. Multiple base stations in a given area serve each terminal after precoding, which can coordinate the inter-cell interference and achieve higher performance. Most previous work in the area has focus on centralized precoding which requires gathering all transmitters’ channel state information (CSI) at central station (CS) through backhaul and then precoding at CS. However, the requirements on backhaul signaling and computational power scales rapidly in large and dense networks, which usually make such fully centralized approaches impractical. In this paper, we study two practical precoding strategies with only local CSI under a relatively realistic scenario. Performance is finally illustrated through numerical simulations.